Teachers' professional competence and wellbeing: Understanding the links between general pedagogical knowledge, self-efficacy and burnout. (October 2016) - Lauermann, Fani; König, Johannes
Abstract: Teachers' professional competence—their professional knowledge, skills, beliefs and motivation—is a critical predictor of teachers' professional wellbeing and success. In a sample of 119 in-service teachers, the present study examined the associations of two aspects of teachers' professional competence—their general pedagogical knowledge (GPK) and self-efficacy—with teachers' likelihood of experiencing burnout, as well as possible differences in these constructs as a function of gender and teaching experience. A path analysis revealed no systematic associations with gender, whereas teaching experience had a curvilinear association with GPK, a negative linear association with self-efficacy, and no significant association with burnout. Mediation analyses suggested that GPK negatively predicted teacher burnout both directly, as well as indirectly via its positive association with teaching self-efficacy. Only teaching-specific but not general self-efficacy functioned as a mediator in these analyses; the identified predictive effects are thus specific to teachers' professional competence. Possible implications for the prevention of burnout are discussed. Highlights: GPK is related to teaching-specific but not to domain-general self-efficacy. GPK indirectly negatively predicted teacher burnout, via teaching self-efficacy. GPK directly negatively predicted depersonalization, controlling for self-efficacy. There is a curvilinear association between teachers' GPK and teaching experience.